Therapeutic Potential of the Ranibizumab Port Delivery System in the Treatment of AMD: Evidence to Date - Chen ER (Dove Medical Press, 2020)
Eric R Chen,1 Peter K Kaiser2 1School of Medicine, Case Western Reserve University, Cleveland, OH, USA; 2Cole Eye Institute, Cleveland Clinic Foundation, Cleveland, OH, USACorrespondence: Peter K KaiserCole Eye Institute, Cleveland Clinic Foundation, 9500 Euclid Avenue, Desk i3-125, Cleveland, OH 44195, USATel +1 (216) 444-6702Email kaiserp@ccf.orgAbstract: Age-related macular degeneration (AMD) is one of the leading causes of blindness in older adults worldwide. The advent of intravitreal neutralization of vascular endothelial growth factor (VEGF) has revolutionized the management of patients with neovascular AMD, but current anti-VEGF therapies carry a high threshold of patient burden. The ranibizumab port delivery system (PDS) is an implanted, refillable reservoir that continuously supplies the anti-VEGF medication ranibizumab directly into the vitreous, eliminating the need for frequent intravitreal injections. It has most recently been evaluated in the Phase II LADDER trial demonstrating the efficacy and safety of the PDS, with Phase III trials currently underway. This review presents both the promise and drawbacks of the PDS in the treatment of AMD from the current literature.Keywords: neovascular age-related macular degeneration, ranibizumab, port delivery system, vascular endothelial growth factor